An efficient controlled release strategy for hypertension therapy: Folate-mediated lipid nanoparticles for oral peptide delivery. (July 2020) - Li, Jinhua; Chen, Bin; Yu, Ting; Guo, Mengran; Zhao, Shengnan; Zhang, Yi; Jin, Chaohui; Peng, Xingchen; Zeng, Jun; Yang, Jian; Song, Xiangrong
Graphical abstract: Abstract: Hypertension is an important cardiovascular disease, which need long-term medication. Thus, oral drug delivery system is a preferred route for hypertension patients due to the convenience and compliance. Val-Leu-Pro-Val-Pro (VLPVP, VP5) is an angiotensin converting enzyme inhibitory peptide with antihypertensive effects. However, the oral peptide delivery is faced with obstacles, such as gastric acid, enzyme degradation and intestine barriers. Herein, we developed a controlled release system consisting of a PLGA core encapsulated with VP5 and a folate-decorated lipid shell (FA-VP5-LNPs) for the oral delivery of antihypertensive peptide. The results found that FA-VP5-LNPs exhibited high stability and possessed a controlled release behavior. Besides, FA-VP5-LNPs improved the cellular uptake both in Caco-2 and HT29 cells and enhanced in situ intestinal absorption in SD rats. The in vivo bioavailability study showed a superior oral absorption of FA-VP5-LNPs, and the AUC0-72 h of FA-VP5-LNPs was 30.71-fold higher than that of free VP5. The pharmacodynamics study exhibited that FA-VP5-LNPs maintained strong antihypertensive effect for six days compared with free VP5, which may reduce the frequency of administration and improve patient compliance. In addition, the nano-formulations showed no toxicity to cells and tissues. These promising results suggested that FA-VP5-LNPs could overcome the intestinal barrier and provide a potential strategy for enhancing peptide delivery and improve the antihypertensive effects.